2021
DOI: 10.1038/s41541-021-00309-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunofocusing humoral immunity potentiates the functional efficacy of the AnAPN1 malaria transmission-blocking vaccine antigen

Abstract: Malaria transmission-blocking vaccines (TBVs) prevent the completion of the developmental lifecycle of malarial parasites within the mosquito vector, effectively blocking subsequent infections. The mosquito midgut protein Anopheline alanyl aminopeptidase N (AnAPN1) is the leading, mosquito-based TBV antigen. Structure-function studies identified two Class II epitopes that can induce potent transmission-blocking (T-B) antibodies, informing the design of the next-generation AnAPN1. Here, we functionally screened… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(42 reference statements)
3
10
0
Order By: Relevance
“…Previously we have shown that the UF6b antigen is highly immunogenic in CD1 outbred mice (8). Here we aimed to find the optimally immunogenic dose and ratio of UF6b-NPs to CpG-NPs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously we have shown that the UF6b antigen is highly immunogenic in CD1 outbred mice (8). Here we aimed to find the optimally immunogenic dose and ratio of UF6b-NPs to CpG-NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The ELISAs were performed as previously described (8). Briefly, Nunc Maxisorp 96-well ELISA plates (Fisher Scientific, Waltham, MA, USA) were incubated overnight at 4°C with 1 mg/mL UF6b antigen in 0.1×PBS (pH 7.2).…”
Section: Enzyme Linked Immunosorbent Assaysmentioning
confidence: 99%
See 3 more Smart Citations